المردود التربوي للمدرسة الجزائرية - علي شريف, حورية (Sciences de l'Homme et de la Société, 2012)
من أهم التحديات التي تشغل باستمرار اهتمام القائمين عن التربية والتعليم في الجزائر، الوصول بالمنظومة التربوية إلى مردودية أفضل، وجعل المدرسة الجزائرية مؤسسة ذات جودة عالية بإمكانها تخريج أجيال باستطاعتها مواجهة التحديات الداخلية والخارجية، نظرا للطبيعة الخاصة بالعملية التعليمية دائمة التأثير والتأثر بالمتغيرات العالمية والمحلية. لذا عرفت الجزائر ومنذ الاستقلال تعديلات وإصلاحات متعددة حسب مايتطلبه الواقع المحلي والعالمي وما يفرضه القانون الدولي الجديد، وما تطرحه تداعيات العولمة بأوجهها المختلفة، على نظم المجتمع عامة، وعلى النظام التربوي خاصة.   One of the most important challenges, that are consistently interest people of  Education in Algeria, is to access to the best output of the educational system, and make the Algerian school an institution of high quality, that can produce generations able to face the internal and external challenges; this according to the special nature of the educational process; always affecting and affected by global and local variables .So, Algeria knew, since the independence, multiple modifications and reforms, according to what is required by local and global realities, and imposed by the new international law, and also by the implications of globalization, in its different faces, on the society systems in general, and on the educational system in particular.